THE IMPACT OF THE PANDEMIC ON THE DIGITALIZATION OF EMPLOYMENT IN UKRAINE - Sheketa , E. Yu.; Kykhnii , L. S. (The actual problems of regional economy development, 2020)
The article is devoted to the study of the impact of the Covid-19 pandemic on employment in Ukraine, in particular, on the spread of remote employment and home-based work through information and telecommunication technologies for access to the workplace. The impact of the rapid growth of remote employment during a pandemic, reproducing work as a mixture of virtual and physical experience, will help workers focus on important aspects of organizing their own working time in order to adapt to new work realities. Companies had to create quickly new digital jobs, redesign existing ones, outline business ethics for their employees in online access to all company resources, and provide them with the necessary tools for cooperation and communication, which are necessary for normal financial and economic activities and productivity. Companies that have taken into account the needs of their employees and customers, to ensure their secure online interaction and create harmonious relationships have been able to move to a qualitatively new level of organization of working time in their activities. The level of use of information and communication technologies by domestic enterprises and the dynamics of growth of enterprises that trained their staff in digital skills were studied. Using the methodology of SWOT - analysis, the advantages and disadvantages of the impact of the digitalization process on the structure of employment in the labor market of Ukraine were formed, which allowed to outline the opportunities and threats of further development. It is concluded that the key element of success of leading companies is their staff, employees with active and non-standard thinking and a wide range of digital competencies, the so-called “knowledge workers”, whose main tool is mental activity. Technical solutions for online training, professional development, and acquisition of digital skills and competencies of staff based on free online platforms, mobile applications or computer programs are offered.